Collateral Damage? Labour Market Effects of Competing with China – at Home and Abroad - Sónia Cabral; Pedro S. Martins; Jo\~ao Pereira dos Santos; Mariana Tavares (Institute of Labor Economics (IZA), 2018)
The increased range and quality of China's exports is a major ongoing development in the international economy with potentially far-reaching effects. In this paper, on top of the direct effects of increased imports from China studied in previous research, we also measure the indirect labour market effects stemming from increased export competition in third markets. Our findings, based on matched employer-employee data of Portugal covering the 1991-2008 period, indicate that workers' earnings and employment are significantly negatively affected by China's competition, but only through the indirect 'market-stealing' channel. In contrast to evidence for other countries, the direct effects of Chinese import competition are mostly non-significant. The results are robust to a number of checks and also highlight particular groups more affected by indirect competition, including women, older and less educated workers, and workers in domestic firms.
Keywords: F14; F16; F66; J31; 330; international trade; labour market; matched employer-employee data; China; import competition